2014
DOI: 10.1186/1471-2474-15-302
|View full text |Cite
|
Sign up to set email alerts
|

A stress fracture of the base of the acromion: a case report

Abstract: BackgroundStress fractures of the base of the acromion are rare and tend to progress well when conservatively treated. The need for surgery due to this type of fracture has only been reported in two case reports.Case presentationA 39-year-old patient, manual laborer, with a stress fracture at the base of the acromion that required surgical treatment due to persistent symptoms and consolidation failure.ConclusionWe described a new mechanism of injury for stress fractures of the base of the acromion. After the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Fractures of the acromion and the scapular spine are uncommon in individuals with normal shoulders [ 35 , 36 ] or anatomic prostheses but are frequently encountered in patients with reverse shoulder prostheses. The fracture rate after RSA averages 4 to 5% [ 37 – 39 ] and ranges from 0.5% [ 40 ] to 25% [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fractures of the acromion and the scapular spine are uncommon in individuals with normal shoulders [ 35 , 36 ] or anatomic prostheses but are frequently encountered in patients with reverse shoulder prostheses. The fracture rate after RSA averages 4 to 5% [ 37 – 39 ] and ranges from 0.5% [ 40 ] to 25% [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, while the acromion is a relatively small and irregularly quadrangular bone in anatomical terms, the term ‘acromion’ is used surgically and clinically to indicate a much larger region [ 16 ]. There is an inconsistency in the nomenclature for acromion fracture in the literature [ 17 19 ]. Some authors consider only the area of the anterior bony protrusion from the lateral scapular spine as the acromion, while the rest is referred to as the lateral extension of the scapular spine, or more simply as the scapular spine [ 14 , 15 , 20 – 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is hypothesized in the literature that symptoms from a base of the acromion fracture are unique because the mechanical pull from both deltoid and trapezius results in more symptoms, tendency for instability, and puts the patient at an increased risk of developing pseudoarthrosis. 4 , 9 …”
mentioning
confidence: 99%
“…Described surgical techniques for these fractures include plates and screws, and tension band wiring with or without bone grafting. 4 , 9 Malavolta et al 4 used a standard 6-hole Locking Compression Plate (LCP) with locking screws to achieve the necessary fixation of a fractured acromion. More recently, Kurahashi et al 3 reported the use of a “mesh plate” in 2 acute cases.…”
mentioning
confidence: 99%